(untitled) (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Employee Training is an effort by companies or organizations or agencies to improve their performance through increasing employee productivity. As far as our research results are concerned, there is a lot of literature related to employee training, but there is no bibliometric analysis of research articles related to employee training. This research is aimed at analyzing classification, identifying trends, and analyzing opportunities for research topics related to employee training in the future. This research uses a combination of the Publish and Perish, Mendeley, and Vosviewer applications as well as a 5-stage methodology on the Scopus database. By using the keyword "Employee Training" which represents employee training, the results of research analysis related to this keyword in 2018-2023 can be classified into three clusters. The Three Clusters Include Research on Employee Training Linked to Training Impact, Employee Training Linked to Training Evaluation, and Employee Training Linked to Training Models. Meanwhile, research topics that are widely used today are models, technology, workers and experience. There are several research topics regarding employee training that have not been carried out much, including jobs, challenges for the future, and participation in gamification methods which could become research topic opportunities in the future.